Crack initiation in PMMA plates with circular holes considering kinetic energy and nonlinear elastic material behavior. (April 2023) - Chen, Xi; Doitrand, Aurélien; Godin, Nathalie; Fusco, Claudio
Abstract: The coupled criterion (CC) of finite fracture mechanics (FFM) is extended to assess crack initiation in PMMA specimens with holes under quasi-static loading considering nonlinear elastic (NLE) material model and considering the kinetic energy variation in the energy balance. If dynamic aspects are disregarded, the failure stress predicted using the CC for either linear elastic (LE) material model or NLE material model is underestimated compared to the one measured experimentally. A better representation of the failure stress variation as a function of the hole size is obtained considering constant crack velocity profiles and velocities in the range [550–900] m/s (LE material model) or [400–600] m/s (NLE material model). The predicted failure stresses also depend on the crack velocity profile. Highlights: Dynamic implementation of the CC considering material nonlinearities. Failure stress increase with increasing mean crack velocity. Predicted failure stress influenced by the crack velocity profile. Improvement of the failure stress prediction considering dynamic aspects.